A COMPARATIVE ANALYSIS OF MALE AND FEMALE WHO BUY ON INSTAGRAM ONLINE SHOP - Rompas, Chrisly Yosua; Massie, James D.D; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: This research aims to see if there is significant difference between Male and Female customers of Instagram Online Shop based on Electronic Word-of-Mouth and Perceived Ease-of-Use. This research type is descriptive with quantitative method, using Independent Sample T-Test as analytical tool. The sample size of this research is 100 Customer divided to 50 Male and 50 Female as respondents. Simple Random Sampling was used to collecting data through questionnaire. The result shows that there is no significant difference based on Electronic Word-of-Mouth and there is significant difference based on Perceived Ease-of-Use between Male and Female customers. Female gives bigger perception toward Perceived Ease-of-Use because demographically most of Instagram Users are Females, it makes them easier and get used to using Instagram Feature rather than Male. Future Recommendation for Online Shop owner to give clear information about the product that they are going to sell because each people have different abilities and experience regarding using Instagram Features. Hence it can increase sales if they can focus well enough for the improvement. Keywords: electronic word-of-mouth, perceived ease-of-use, gender differences, independent sample t-test.